2017
DOI: 10.1177/0963721417721526
|View full text |Cite
|
Sign up to set email alerts
|

Religious Communities and Human Flourishing

Abstract: Participation in religious services is associated with numerous aspects of human flourishing, including happiness and life satisfaction, mental and physical health, meaning and purpose, character and virtue, and close social relationships. Evidence for the effects of religious communities on these flourishing outcomes now comes from rigorous longitudinal study designs with extensive confounding control. The associations with flourishing are much stronger for communal religious participation than for spiritual-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 37 publications
3
60
0
4
Order By: Relevance
“…44 It is perhaps the coming-together of shared values and enhanced social integration that provides the health benefits. 1 , 16 , 45 This may also help to explain why the associations of service attendance with many outcomes in this study remained robust, even after adjusting for other major aspects of social integration.…”
Section: Discussionmentioning
confidence: 70%
“…44 It is perhaps the coming-together of shared values and enhanced social integration that provides the health benefits. 1 , 16 , 45 This may also help to explain why the associations of service attendance with many outcomes in this study remained robust, even after adjusting for other major aspects of social integration.…”
Section: Discussionmentioning
confidence: 70%
“…Different aspects may contribute to and influence how people appraise the many facets of their lives, ranging from individual characteristics that distinguish between happy and unhappy personalities, to values people consider important and worth pursuing in life or the fulfillment of social needs (Balzarotti et al, 2016; Diener et al, 2018; Schwartz and Sortheix, 2018). Among others, a growing body of research investigates the role that spirituality and religiosity play in individuals’ self-perceived well-being, identifying a positive effect of religion and spirituality on many psychosocial and health-related outcomes across the lifespan (e.g., Fabricatore et al, 2000; Fry, 2000; Mueller et al, 2001; George et al, 2002; Levin and Chatters, 2008; Krause, 2011; VanderWeele, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The significance of income was supported by Easterlin et al [32] who averred that an increase in income and consumption enables the satisfaction of needs and therefore leads to increase in wellbeing. The significance of religion is corroborated by a multitude of studies including Vanderweele [12] who found that active religious involvement has been found to increase longevity, Lim [14] who found significant relationships between Church attendance, personal prayer, belief in God and psychological well-being, and Ismail and Desmukh [18] who found that many people find inner peace and contentment by engaging in varied forms of religious rituals and rites.…”
Section: Discussionmentioning
confidence: 94%
“…Individuals have been known to use religion as a means of reducing the distressing effects of their day-to-day activities, coping with fears, and/or feeling confident that nothing bad will happen to them [11]. Active religious involvement has been found to reduce mortality rate by 25% to 35% over a period of 10 to 15 years; participation in public religious practices, such as church attendance, increased the chances of living longer by 43% [12]. Also in a study investigating the role of religion on health and well-being, positive relationship was revealed between religious participation and health outcome [13].…”
Section: Introductionmentioning
confidence: 99%